Exploring the molecular characteristics of inflammatory bowel disease from the perspective of hypoxia-related genes - Zheng, Lei; Mou, Lin; Hao, Lingying; Chen, Rui; Wang, Yifei; Yu, Miao; Zhang, Xueyan (Frontiers in Pharmacology, 2025)
BackgroundInflammatory bowel disease (IBD) constitutes a chronic inflammatory disorder affecting the gastrointestinal tract, characterized by a multifaceted pathogenesis that encompasses genetic, environmental, and immunological influences. The role of hypoxia in IBD pathophysiology has been recognized. However, the specific genes associated with hypoxia and their potential for diagnostic application remain inadequately investigated.MethodsThree datasets (GSE48958, GSE75214, and GSE179285) were procured from the Gene Expression Omnibus (GEO) database through the GEOquery package, all sourced from human colon tissue. Hypoxia-related genes (HRGs) were extracted from the GeneCards database. Data preprocessing involved mitigating batch effects via the sva package and normalizing with the limma package. The differential expression analysis, conducted with limma, uncovered 475 differentially expressed genes (DEGs), comprising 152 downregulated and 323 upregulated genes. A subset of 23 hypoxia-related differentially expressed genes (HRDEGs), including ADM, BHLHE40, CCL2, and CD274, was identified by intersecting DEGs with HRG sets.ResultsThe analysis identified 475 DEGs within the aggregated dataset, with 323 exhibiting upregulation and 152 downregulation. Enrichment analysis highlighted the significant role of these HRDEGs in critical processes such as angiogenesis and the HIF-1 signaling pathway. A diagnostic model (DM) integrating 13 HRDEGs exhibited high accuracy, achieving an area under the curve (AUC) exceeding 0.9 across various datasets. Immune infiltration analysis revealed substantial disparities in 13 distinct immune cell populations when comparing high-risk and low-risk cohorts.ConclusionsIn summary, this investigation underscores the pivotal function of HRGs in IBD's pathogenesis and introduces a reliable DM grounded in these genetic factors. The findings accentuate the relevance of hypoxia-responsive pathways in IBD and enhance understanding of immune cell dynamics across differing risk profiles. Subsequent investigations should seek to confirm these biomarkers in clinical contexts and investigate therapeutic strategies targeting hypoxia-related pathways for effective IBD management.